2021
DOI: 10.1177/17579139211011496
|View full text |Cite
|
Sign up to set email alerts
|

The influence of residential greenness on mortality in the Asia-Pacific region: a systematic review and meta-analysis

Abstract: Aims: To critically appraise the evidence of the impact of exposure to salutogenic green environment on mortality, which is an important endpoint in epidemiological and clinical studies. Methods: We searched for studies published and indexed in three databases (PubMed, AMED, and CINAHL Plus) from inception until 31 March 2020, complemented with a search of cited literature for articles describing the effects of greenness on mortality in Asia-Pacific region. Eligible articles were screened and data were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…We defined residential greenness as the annual mean NDVI/EVI during 2016–2018 (the 3 years before the survey) within the 250, 500, and 1,000 m buffer zones around the residential address of each participant, for easier comparison with similar studies ( 27 , 28 ). The 500 m radius of the buffer zone has been widely used in many similar studies to measure residential greenness ( 29 ), so the results from the 500 m buffer zone were presented as the main results.…”
Section: Methodsmentioning
confidence: 99%
“…We defined residential greenness as the annual mean NDVI/EVI during 2016–2018 (the 3 years before the survey) within the 250, 500, and 1,000 m buffer zones around the residential address of each participant, for easier comparison with similar studies ( 27 , 28 ). The 500 m radius of the buffer zone has been widely used in many similar studies to measure residential greenness ( 29 ), so the results from the 500 m buffer zone were presented as the main results.…”
Section: Methodsmentioning
confidence: 99%
“…Experts are suggesting greenness as a solution that can help curb climate change [43] by providing the co-benefits of improving resiliency and recovery from the impacts of climate change [44,45]. While some pioneering studies focused on specific climate change impacts (extreme heat, heat island impact [46][47][48] and air quality interactions [49]), others focused on health interactions in specific regions (Asia, Europe) [50][51][52]. We review research on the challenges exacerbated by climate change and show how greenness can help accomplish climate change adaptation and mitigation goals while also enhancing human health.…”
Section: Adaptationmentioning
confidence: 99%
“…In recent years, greenness has been a research hotspot in the environmental epidemiology. Greenness has been generally associated with health benefits in humans, such as reduced all-cause mortality [ 4 , 5 ], reduced incidence of adverse pregnancy outcomes [ 6 , 7 ], and reduced risk of overweight and obesity [ 8 , 9 ]. Therefore, one study suggested that greenness was considered to act on health through various ways, and these were divided into three fields – reducing harmful exposure, resilience, and building capacity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%